Pengaruh Pendapatan Orang Tua dan Lingkungan Teman Sebaya terhadap Perilaku Konsumtif Mahasiswa Program Studi Manajemen Universitas Kristen Indonesia Toraja - Yusris Pakiding; Agustinus Mantong; Grace Siriati Mengga (Prosiding Seminar Nasional Manajemen dan Ekonomi, 2025)
The purpose of this study was to determine whether there is an influence of parental income and peer environment on the consumer behavior of students studying in the Management Study Program at the Indonesian Christian University of Toraja. Data collection procedures for this study included observation, questionnaires, and documentation. The method used in this study was a quantitative method using the Simple Linear Regression method and processed using SPSS 26. The sample collection technique used was nonprobability sampling with a purposive sampling technique where the sampling technique was based on certain criteria or considerations. The results of the study showed that the t-test on the Parental Income variable had a calculated t value > t table with a value of (3.409) < (1.664). The Parental Income variable has a positive and significant influence on the Consumer Behavior of Students Studying in the Management Study Program at the Indonesian Christian University of Toraja. The t-test on the Peer Environment had a calculated t value > t table with a value of (4.279) < (1.664). The Peer Environment has a positive and significant influence on the Consumer Behavior of Students Studying in the Management Study Program at the Indonesian Christian University of Toraja. The f-test has a significance value of 0.000 < 0.05, which means that parental income and peer environment have a simultaneous and significant influence on the consumer behavior of students in the Management Study Program at the Indonesian Christian University of Toraja.